Why is UIP peripheral?. Issue 8 (3rd August 2022) - Shakil, Faariah; Snijder, Juan; Salvatore, Mary M.
ABSTRACT: Introduction: The radiology pattern associated with IPF is called UIP. It is unique because unlike any other form of fibrosis it is peripheral in its distribution. We investigated the peripheral nature of UIP and why it was a key feature of IPF the deadliest of the ILDS. Areas covered: It is not enough to say that UIP is peripheral but instead as scientists we must ask ourselves why it is peripheral. This review dives into the published hypothesis that includes vascular insult, tensile forces, microaspiration, and inflammation and looks at the pros and cons for each argument, and ultimately comes to its own conclusion. PubMed searches using the below keywords were used to identify papers that described pathogenesis of IPF with regard to a particular theory. Expert opinion: In this paper, we will review four ideas that support why UIP is peripheral and propose the most likely explanation given what is currently known about the pathophysiology of IPF.